Multilocus Genotypes of Relevance for Drug Metabolizing Enzymes and Therapy with Thiopurines in Patients with Acute Lymphoblastic Leukemia - Stocco, Gabriele; Franca, Raffaella; Verzegnassi, Federico; Londero, Margherita; Rabusin, Marco; Decorti, Giuliana (Frontiers in Genetics, 2013)
Multilocus genotypes have been shown to be of relevance for using pharmacogenomic principles to individualize drug therapy. As it relates to thiopurine therapy, genetic polymorphisms of TPMT are strongly associated with the pharmacokinetics and clinical effects of thiopurines (mercaptopurine and azathioprine), influencing their toxicity and efficacy. We have recently demonstrated that TPMT and ITPA genotypes constitute a multilocus genotype of pharmacogenetic relevance for children with acute lymphoblastic leukemia (ALL) receiving thiopurine therapy. The use of high-throughput genomic analysis allows identification of additional candidate genetic factors associated with pharmacogenetic phenotypes, such as TPMT enzymatic activity: PACSIN2 polymorphisms have been identified by a genome-wide analysis, combining evaluation of polymorphisms and gene-expression, as a significant determinant of TPMT activity in the HapMap CEU cell lines and the effects of PACSIN2 on TPMT activity and mercaptopurine induced adverse effects were confirmed in children with ALL. Combination of genetic factors of relevance for thiopurine metabolizing enzyme activity, based on the growing understanding of their association with drug metabolism and efficacy, is particularly promising for patients with pediatric ALL. The knowledge basis and clinical applications for multilocus genotypes of importance for therapy with mercaptopurine in pediatric ALL is discussed in the present review.